2020
DOI: 10.5093/jwop2020a6
|View full text |Cite
|
Sign up to set email alerts
|

Appreciation and Illegitimate Tasks as Predictors of Affective Well-being: Disentangling Within- and Between-Person Effects

Abstract: This study examines the effects of appreciation and illegitimate tasks on affective well-being. As empirical results often refer to inter-individual effects but are interpreted in terms of intra-individual effects, we try to disentangle the two. In longitudinal multilevel structural equation models with data of 308 participants, appreciation predicted affective wellbeing in the expected direction both on the within-level and the between-level, whereas illegitimate tasks had a stronger effect on the between lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 110 publications
2
20
0
3
Order By: Relevance
“…Relational devaluation may be communicated directly, for instance by incivility (Cortina et al, 2017) or unfair criticism (Krings et al, 2015) but also by not communicating respect and appreciation people feel they deserve, for instance by not acknowledging achievements (Miller, 2001;Pfister et al, 2020b;Pfister et al, 2020a). However, SOS theory suggests that such messages may also be expressed more indirectly, for instance through job design.…”
Section: Stress-as-offense-to-self (Sos)mentioning
confidence: 99%
“…Relational devaluation may be communicated directly, for instance by incivility (Cortina et al, 2017) or unfair criticism (Krings et al, 2015) but also by not communicating respect and appreciation people feel they deserve, for instance by not acknowledging achievements (Miller, 2001;Pfister et al, 2020b;Pfister et al, 2020a). However, SOS theory suggests that such messages may also be expressed more indirectly, for instance through job design.…”
Section: Stress-as-offense-to-self (Sos)mentioning
confidence: 99%
“…Focusing on mediation over time, the analyses presented here complement recently published multilevel analyses based on the same data, focusing on disentangling within-person and between-person effects of appreciation and illegitimate tasks (Pfister et al , 2020). Appreciation was associated with well-being in terms of enthusiasm, contentment, depression and anxiety on both the interpersonal and the intrapersonal level.…”
mentioning
confidence: 99%
“…Furthermore, it buffered associations between illegitimate task and anxiety as well as contentment on the intrapersonal level. Pfister et al (2020) focused on well-being in terms of high/low arousal and positive/negative valence, and the methodology allowed only distinguishing between-person and within-person effects but no longitudinal prediction. In contrast, the current paper tests a longitudinal mediation model on the between-person level, using job satisfaction as outcome variable and feelings of success and resentments towards one's organization as mediators.…”
mentioning
confidence: 99%
“…The Spanish version of the BITS showed good internal consistency for both the whole scale (Cronbach’s alpha = 0.857) and the subscales (see Table 3 ). Moreover, many studies have demonstrated good reliability for the whole scale (Cronbach’s alpha = 0.79–0.88), the unnecessary task subscale (Cronbach’s alpha = 0.76–0.91), and the unreasonable task subscale (Cronbach’s alpha = 0.73–0.91) ( Jacobshagen, 2006 ; Semmer et al, 2010 ; Pereira et al, 2014 ; Muntz et al, 2019 ; Pfister et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SOS theory not only describes threats to self-esteem but also assesses boosts to self-esteem ( Semmer et al, 2007 ; Pfister et al, 2020b ), which imply success and failure, meaning that workers who achieve goals or make progress toward goals are less able to develop SIN ( Semmer et al, 2007 , 2019 ). Similar to SIN, SAD can be lowered by positive affect and satisfaction ( Semmer et al, 2019 , 2020 ; Pfister et al, 2020a , b ; Stein et al, 2020 ). Therefore, these two factors are the principal states of SOS theory.…”
Section: Introductionmentioning
confidence: 99%